Prevalence of self-reported noncommunicable diseases in grassroot-level health worker of Petlad taluka: A cross-sectional study - Charvi P. Mistry; Dinesh J. Bhanderi (Journal of Family Medicine and Primary Care, 2023)
Context: Noncommunicable diseases (NCDs) kill 41 million people each year globally. The financial burden of NCDs, including lifelong and expensive treatment with loss of income, forces many people into poverty. Healthcare workers (HCWs) are an essential group of the workforce in building a healthier society. They must choose a healthy lifestyle to have better health for themselves. Aim: To estimate the prevalence of self-reported NCDs in grassroot-level HCWs of Petlad taluka along with the study of various healthcare and lifestyle practices among them Methods and Material: In this cross-sectional study, grassroot-level HCWs of Petlad taluka of Anand district were given a self-administered questionnaire, which included their demographic details, their current health status, and health practices followed by them Statistical Analysis: The data collected were entered in Microsoft Excel-2019 and analysed by SPSS version 15. Descriptive analysis and univariate analysis were performed. Results: NCDs’ prevalence was 10.2%. Hypertension and diabetes were the commonest. Nearly 50% HCWs have their body mass index in a normal range. The majority of them were aware of healthy diet practices and exercise. Conclusions: Our study reported a lower prevalence of NCDs than other studies (50%). Dietary practices appear to be healthy, but a significant proportion of them are overweight. The majority of them prefer to consult at a government hospital. Healthy behaviour and practices should be encouraged and maintained in HCWs.